2006
DOI: 10.1021/ef0503515
|View full text |Cite
|
Sign up to set email alerts
|

Nonpolar Compositional Analysis of Vacuum Gas Oil Distillation Fractions by Electron Ionization Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: We analyzed three vacuum gas oil distillation fractions, 295−319 °C, 319−456 °C, and 456−543 °C, with a home-built external electron ionization (EI) 7 T Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometer. EI at 10 eV allows soft ionization of aromatic compounds in the vacuum gas oil range. Unambiguous elemental composition assignment provides insight into compositional variations at the molecular level; for example, ultrahigh resolving power (m/Δm 50% ≈ 300 000 at m/z 300) and mass accuracy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 59 publications
9
55
0
Order By: Relevance
“…The number of assigned S 1 compounds (compounds containing one sulfur atom) from Pd-1 was 11, 94, and 106 in the three boiling ranges in increasing order of distillation temperature, and the number of S 1 compounds in Pd-2 was 188, 225, and 281, respectively. This corroborates the trend of an increasing number of S 1 members with increasing boiling temperature as was observed by low-voltage electron ionization FT-ICR MS [15]. Information on the molecular weight distribution pattern is given by the number-average molecular weight, M n , and the weight-average molecular weight, M w. These numbers were calculated for S 1 compounds in Pd-2 of all three VGOs [22].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The number of assigned S 1 compounds (compounds containing one sulfur atom) from Pd-1 was 11, 94, and 106 in the three boiling ranges in increasing order of distillation temperature, and the number of S 1 compounds in Pd-2 was 188, 225, and 281, respectively. This corroborates the trend of an increasing number of S 1 members with increasing boiling temperature as was observed by low-voltage electron ionization FT-ICR MS [15]. Information on the molecular weight distribution pattern is given by the number-average molecular weight, M n , and the weight-average molecular weight, M w. These numbers were calculated for S 1 compounds in Pd-2 of all three VGOs [22].…”
Section: Resultssupporting
confidence: 86%
“…This procedure allows the use of ESI for the analysis of PASHs. Recently, continuous-flow field desorption [14] and lowvoltage electron ionization [15] coupled with FT-ICR MS were reported for the study of VGOs of different origin and of different boiling ranges, respectively. Other reports [16] compared the use of the derivatization method using ESI detection with atmospheric pressure photoionization (APPI) and indicated that the range in the first case mentioned was limited to double bond equivalent (DBE) values below 15 and therefore the APPI approach was favored.…”
Section: Introductionmentioning
confidence: 99%
“…The resolution of FT-ICR MS was improved by increasing the magnetic field to 5.6 T SCM in the compositional analysis of raw diesel fuel 13) . Different boiling cuts of VGO were characterized by 7 T SCM with low voltage EI to sup press fragmentation and demonstrated an increase in the observed mass range up to m/z 500 depending on the boiling temperature of the VGO cut 14) . Heavy distillate is believed to contain much higher molecular weight species than m/z 500 4) .…”
Section: Application Of In-beam Ei Ft-icr Ms For Ar Vgo and Vacuum mentioning
confidence: 99%
“…1 FT-ICR MS was shown to be effective for identifying the molecular composition of crude oils. [2][3][4][5][6][7][8][9][10][11][12] One of the most important goals of petroleomics is to predict the reactivities and properties of crude oils based on molecular information, which is obtained using high-resolution mass spectroscopy. Interpretation of high-resolution mass spectra can cause difficulties because of the large amounts of information contained in each spectrum.…”
Section: Introductionmentioning
confidence: 99%